Flipped Classroom in Subject of Entrepreneurship and Management as Active Learning - De Los Ángeles Lucas Zambrano, María; María San Andrés Laz, Esthela; Fernando Pazmiño Campuzano, Marcos (International Journal of Psychosocial Rehabilitation, 2020)
The flipped classroom is a model developed within the framework of educational innovation and the use of technological resources that consists of investing in the way in which educational knowledge is explained in order to obtain a greater amount of time in the classroom. To favor the practical application of the contents, it favors that the student prior to the development of a class can access the theoretical approaches so that later these are practiced in the classroom so that the detected difficulties are overcome. In the subject of Entrepreneurship and Management, this active learning methodology allows students to have a direct approach with the synthesized contents so that later in the development of activities in the classroom, the student actively participates in their learning, favoring the use of time and assimilation of the contents. Therefore, through research, the aim is to analyze the flipped classroom methodology applied in the discipline of entrepreneurship and management to promote active learning. As a methodology, the exploratory systematic review with a qualitative approach is adopted, with which it is oriented to carry out the synthesized bibliographic review on the Flipped Classroom and active learning. The technique used was desk research to obtain information through existing data. The analysis and discussion of specialized information allowed establishing the advantages of the methodology and its benefits for the active learning of students in the subject of entrepreneurship and management.